Psychological resilience of emergency nurses during COVID-19 epidemic in Shanghai: A qualitative study - Jinxia Jiang; Yue Liu; Peng Han; Pengjia Zhang; Haiyan Shao; Hu Peng; Xia Duan (Frontiers Media S.A., 2022)
BackgroundIn early 2022, an outbreak of Coronavirus Disease 2019 (COVID-19) occurred in Shanghai, China. The spread of the epidemic put a large amount of stress on the local healthcare system, especially emergency nurses (ENs), which may affect their well-being and performance. Enhancing the psychological resilience of ENs during COVID-19 pandemic may improve job satisfaction, retention, and public health emergency response. However, few studies have researched the perception and psychological resilience of ENs during COVID-19 pandemic.ObjectiveTo understand ENs' perception and psychological resilience and their coping strategies with adversity during COVID-19 in Shanghai, as well as factors associated with psychological resilience.MethodsThis qualitative study was conducted using a phenomenological approach. A total of 17 ENs from a 3rd level hospital in Shanghai were selected using a method of purposive sampling. Between April and May 2022, in-depth semi-structured interviews and Colaizzi seven-step method were performed for data collection and analysis.ResultsThe investigation discovered three themes and nine subthemes. The first theme is "risk factors." Risk factors for ENs to remain resilience are sudden multiplication of workload, stressful of screening of infected patients, and the support nurses being unfamiliar with the procedure. The second theme is "promoting factors." ENs emphasized the importance of management assurance and humanistic care, as well as social support. They recognized adversity and resilience, and used self-management strategies to cope with the situation. The third theme is "motivated by altruism." ENs were driven by altruism to respond to adversity with a positive attitude. They realized their self-worth by helping patients with a sense of sacred mission.ConclusionsPsychological resilience is not a stable psychological characteristic but a constantly changing process that is affected by internal and external factors. Enhancing resilience of ENs during the COVID-19 pandemic may improve work satisfaction, retention, and public health emergency response. Adequate preparation before a pandemic, reasonable arrangement, a trustworthy working atmosphere, encouragement and improvement of individual and collective strategies for nurses to cope with adversity, timely rewards, and nurse empowerment, as well as counseling and training, can be used to enhance psychological resilience of ENs.